The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fvets.2020.616882
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Chest Ultrasonography in Predicting Diagnosis in Non-emergency Small Animal Patients With Lung Parenchymal and Pleural Disease

Abstract: Chest ultrasonography has become an indispensable tool for pulmonary specialists in human medicine, but its current use in dogs and cats is primarily for emergency. The diagnostic performances of various ultrasonographic features other than comet-tail artifacts are of limited information in veterinary literatures. Therefore, the aims of this retrospective study were to investigate ultrasonographic findings in feline and canine respiratory patients with lung parenchymal and pleural space diseases, and to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…In a study on dogs and cats, ndings of ultrasound alterations were associated with a diagnosis of pneumonia. These alterations consisted of thickened or irregular pleura (p = 0.034), consolidation (p = 0.032) and absence of nodular lesion or mass (p < 0.001) (Lin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on dogs and cats, ndings of ultrasound alterations were associated with a diagnosis of pneumonia. These alterations consisted of thickened or irregular pleura (p = 0.034), consolidation (p = 0.032) and absence of nodular lesion or mass (p < 0.001) (Lin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consolidations may be focal, partial or lobar (Lin et al 2020). According to the appearance and location, it is possible to differentiate pneumonia from atelectasis due to tissue resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic ultrasonography and ultrasound-guided FNAs/biopsy have been studied extensively in human patients with different kinds of respiratory pathology and were reported to be a valuable tool in small animals with noncardiac intrathoracic disease. 11,12,13,14 In the study by Lin et al, 15 it was reported that the presence of a "nodular or mass-like lesion" and a "consolidated lesion with heteroechogenicity" are significantly associated with pulmonary neoplasia, and although a definitive diagnosis cannot be based merely on the ultrasonographic appearance of a lesion, some characteristics could help predict the underlying aetiology. Similarly, in the present study, sonographic assessment of the thorax allowed further characterisation of the tumor that appeared as a ''mass-like lesion'' in both cases, and ultrasound-guided FNAs allowed a definitive diagnosis to be made in Case 1.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could include different NHP species to confirm the applicability of LUS among species. In addition, it could also include other animal species like dogs and cats in which LUS has proven to be a useful technique but also warrants further investigation to use as a stand-alone imaging modality (39,40). Moreover, to assess the full potential of LUS in NHPs, the effect of different levels of disease severity with respect to the diagnostic efficacy of LUS over CT needs to be evaluated probably in other lung disease models like tuberculosis or influenza (41,42).…”
Section: Discussionmentioning
confidence: 99%